USE OF ARTIFICIAL INTELLIGENCE ON MUSICAL ART LESSONS IN PRIMARY EDUCATION (IN WARTIME CONDITIONS) - Vladymyrova Алла (Journal of Information Technologies in Education (ITE), 2025)
The article examines the peculiarities of the use of artificial intelligence (Suno. AI project) in music lessons in primary education in the conditions of distance learning during wartime. Attention is focused on the restructuring of the psychological and pedagogical activities of the music teacher and primary education teacher in the process of introducing artificial intelligence Suno AI, as an innovative system that automates the process of creating music and has its own key characteristics, with the help of which students learn to analyze musical works, musical parameters, master musical terminology. It has been proven that experimenting with various musical effects enables students, under the guidance of a teacher, to develop their own musical intelligence, musical auditory representations, sense of rhythm, imagination and fantasy. The work of teachers in the field of musical art is characterized, as during the war they suffer from the lack direct "live" contact with students, in the process of learning songs, vocal exercises, emotional experience of song texts. An introduction to Suno artificial intelligence is offered. AI, which will practically help to interest teachers and students in creating and implementing interactive music studies, music games and quizzes, testing their own knowledge in the field of musical art. The study explores the integration of artificial intelligence in music education through various interactive and creative tasks, such as the quiz “Guess the Melody,” “Instrumentalist Battle,” “Musical Crosswords,” “Music Marathon,” “Thesaurus of Musical Terms,” “Composers,” and the music salon “Impromptu.” These activities facilitate the consolidation of theoretical knowledge, the practical application of virtual musical instrument simulators, and the enhancement of students’ creative potential. The use of AI in primary music education, particularly tools like Suno.AI is viewed as highly promising, especially in the context of distance learning, which remains relevant in Ukraine under martial law. AI integration contributes to the design of innovative educational tasks, the development of students’ emotional and imaginative capacities, and supports teachers in acquiring contemporary digital tools for enriching and modernizing music lesson content.